A single-molecular twin rotor: correlated motion of two pyrimidine rings coordinated to copper. Issue 14 (13th January 2015) - Takara, Yusuke; Kusamoto, Tetsuro; Masui, Tatsuya; Nishikawa, Michihiro; Kume, Shoko; Nishihara, Hiroshi
Abstract : A single molecular twin rotor comprising a copper complex exhibits the correlation of the motions of two coordinated pyrimidine rings. Abstract : We describe the two correlated rotational motions of pyrimidine rings in 4, 4′-dimethyl-2, 2′-bipyrimidine ligated to Cu(i ). The two pyrimidine rings delimited by anthryl and phenanthroline groups rotate to afford three isomers. 1 H NMR measurements revealed that the two rotational processes were activated at different temperatures. Cyclic voltammetry gave the kinetic and thermodynamic parameters that provide clear evidence of the correlation between the two rotational steps.